A Comparative Study on Passive Vibration Damping in Thin Carbon Nanotube Based Hybrid Composite Spherical Shell Panel. (2016) - Swain, Ashirbad; Roy, Tarapada; Nanda, Bijoy Kumar
Abstract: The present article deals with the vibration problem associated with thin carbon fiber reinforced composite (CFRC) shell structures that can be mitigated by addition of carbon nanotubes (CNTs) in the polymer matrix phase of such CFRC structures. Mori-Tanaka in conjunction with strength of material method has been employed to obtain the elastic properties of such hybrid composite. Shell structure is discretized by eight noded shell element having five degree of freedom at each node where stress resultant-type Koiter's shell theory is applied. Impulse response using Duhamel integral and frequency response analysis have been carried out to analyze the damping phenomena of hybrid composite structure considering Raleigh damping. Results revealed that there are profound influence of carbon nanotube content on the dynamic response of the system. It is also found that the both the damping and stiffness of the structure is increased by the inclusion of carbon nanotubes.